New horizons for catalysis disclosed by supramolecular chemistry - Olivo, Giorgio; Capocasa, Giorgio; Del Giudice, Daniele; Lanzalunga, Osvaldo; Di Stefano, Stefano (Chemical Society reviews, 2021)
The adoption of a supramolecular approach in catalysis promises to address a number of unmet challenges, ranging from activity (unlocking of novel reaction pathways) to selectivity (alteration of the innate selectivity of a reaction, e.g. selective functionalization of C-H bonds) and regulation (switch ON/OFF, sequential catalysis, etc. ). Supramolecular tools such as reversible association and recognition, pre-organization of reactants and stabilization of transition states upon binding offer a unique chance to achieve the above goals disclosing new horizons whose potential is being increasingly recognized and used, sometimes reaching the degree of ripeness for practical use. This review summarizes the main developments that have opened such new frontiers, with the aim of providing a guide to researchers approaching the field. We focus on artificial supramolecular catalysts of defined stoichiometry which, under homogeneous conditions, unlock outcomes that are highly difficult if not impossible to attain otherwise, namely unnatural reactivity or selectivity and catalysis regulation. The different strategies recently explored in supramolecular catalysis are concisely presented, and, for each one, a single or very few examples is/are described (mainly last 10 years, with only milestone older works discussed). The subject is divided into four sections in light of the key design principle: (i) nanoconfinement of reactants, (ii) recognition-driven catalysis, (iii) catalysis regulation by molecular machines and (iv) processive catalysis. Recent advancements in supramolecular catalysis are reviewed, which show the potential of related tools when applied to organic synthesis. Such tools are recognized as innovative instruments that can pave the way to alternative synthetic strategies.